2015
DOI: 10.3340/jkns.2015.58.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Low Grade Myofibroblastic Sarcoma Occurred in the Scalp

Abstract: Low-grade myofibroblastic sarcoma (LGMS) is a rare sarcoma with myofibroblastic differentiation. LGMS has a propensity for local recurrence and is associated with a low risk of metastatic spread. A 26-year-old man presented with a 12-month history of a slow growing palpable hard mass in the right parietal scalp. Enhanced CT scan of head showed a 3×4 cm sized well-defined and heterogeneously enhancing scalp mass. The patient underwent excision of the tumor. The histological and immunohistochemical features were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Non-English literature [6] 1 28 0/1 Head&neck 1 S 1 R 1 Roth et al [7] 1 46 0/1 Trunk 1 S 1 NR 1 San Miguel et al [8] 1 51 0/1 Extremity 1 S 1 NR 1 Morgan et al [9] 1 46 0/1 Trunk 1 S 1 NR 1 Tajima et al [10] 1 64 0/1 Trunk 1 S 1 NA 1 Laco et al [11] 1 24 0/1 Head&neck 1 S 1 NR 1 Takahama et al [12] 1 42 1/0 Head&neck 1 RT, CTX 1 DOD 1 Meng et al [13] 14 30. [14] 1 44 1/0 Head&neck 1 S 1 NR 1 Meng et al [15] 3 34 3/0 Head&neck 3 S, RT 3 R 3 Jay et al [16] 1 41 1/0 Head&neck 1 S 1 NR 1 Eisenstat et al [17] 1 5 0/1 Trunk 1 sudden death NA 1 Agaimy et al [18] 2 60-70 0/2 Trunk 2 S 2 R 2 Nagata et al [19] 1 36 1/0 Extremity 1 S 1 NR 1 Morii et al [20] 1 46 0/1 Trunk 1 S 1 NR 1 Demarosi et al [21] 2 56 1/1 Head&neck 2 S 2 NR 2 Niedzielska et al [22] 1 54 1/0 Head&neck 1 S 1 NR 1 Arora et al [23] 1 38 0/1 Extremity 1 S 1 NR 1 Humphries et al [24] 1 15 0/1 Trunk 1 S 1 NA 1 Montebugnoli et al [25] 1 37 1/0 Head&neck 1 S 1 NR 1 Miyazawa et al [26] 1 65 1/0 Trunk 1 S 1 NR 1 Ni et al [27] 1 41 0/1 Head&neck 1 S 1 NR 1 Yamada et al [28] 1 73 1/0 Head&neck 1 S 1 NR 1 Khosla et al [29] 1 55 1/0 Head&neck 1 S, RT 1 NR 1 Murakami et al [30] 1 24 0/1 Trunk 1 S 1 NR 1 Saito et al [31] 1 50 0/1 Extremity 1 S 1 NR 1 Cai et al (2013) [32] 2 30.5 2/0 Head&neck 2 S 2 NR 2 Oylumlu et al [33] 1 36 1/0 Trunk 1 S, CTX 1 Cardiac metastasis Kordač et al [34] 1 40 1/0 Head&neck 1 S 1 NR 1 Qiu et al [35] 2 37 1/1 Head&neck 2 S 2 NR 1 R 1 Han et al [36] 1 26 1/0 Head&neck 1 S 1 NR 1 Myong et al [37] 1 61 0/1 Trunk 1 S 1 NR 1 Maruyama et al [38] 1 43 0/1 Head&neck 1 S 1 NR 1 Hadjigeorgiou et al [39] 1 55 1/0 Trunk 1 ...…”
Section: Discussionmentioning
confidence: 99%
“…Non-English literature [6] 1 28 0/1 Head&neck 1 S 1 R 1 Roth et al [7] 1 46 0/1 Trunk 1 S 1 NR 1 San Miguel et al [8] 1 51 0/1 Extremity 1 S 1 NR 1 Morgan et al [9] 1 46 0/1 Trunk 1 S 1 NR 1 Tajima et al [10] 1 64 0/1 Trunk 1 S 1 NA 1 Laco et al [11] 1 24 0/1 Head&neck 1 S 1 NR 1 Takahama et al [12] 1 42 1/0 Head&neck 1 RT, CTX 1 DOD 1 Meng et al [13] 14 30. [14] 1 44 1/0 Head&neck 1 S 1 NR 1 Meng et al [15] 3 34 3/0 Head&neck 3 S, RT 3 R 3 Jay et al [16] 1 41 1/0 Head&neck 1 S 1 NR 1 Eisenstat et al [17] 1 5 0/1 Trunk 1 sudden death NA 1 Agaimy et al [18] 2 60-70 0/2 Trunk 2 S 2 R 2 Nagata et al [19] 1 36 1/0 Extremity 1 S 1 NR 1 Morii et al [20] 1 46 0/1 Trunk 1 S 1 NR 1 Demarosi et al [21] 2 56 1/1 Head&neck 2 S 2 NR 2 Niedzielska et al [22] 1 54 1/0 Head&neck 1 S 1 NR 1 Arora et al [23] 1 38 0/1 Extremity 1 S 1 NR 1 Humphries et al [24] 1 15 0/1 Trunk 1 S 1 NA 1 Montebugnoli et al [25] 1 37 1/0 Head&neck 1 S 1 NR 1 Miyazawa et al [26] 1 65 1/0 Trunk 1 S 1 NR 1 Ni et al [27] 1 41 0/1 Head&neck 1 S 1 NR 1 Yamada et al [28] 1 73 1/0 Head&neck 1 S 1 NR 1 Khosla et al [29] 1 55 1/0 Head&neck 1 S, RT 1 NR 1 Murakami et al [30] 1 24 0/1 Trunk 1 S 1 NR 1 Saito et al [31] 1 50 0/1 Extremity 1 S 1 NR 1 Cai et al (2013) [32] 2 30.5 2/0 Head&neck 2 S 2 NR 2 Oylumlu et al [33] 1 36 1/0 Trunk 1 S, CTX 1 Cardiac metastasis Kordač et al [34] 1 40 1/0 Head&neck 1 S 1 NR 1 Qiu et al [35] 2 37 1/1 Head&neck 2 S 2 NR 1 R 1 Han et al [36] 1 26 1/0 Head&neck 1 S 1 NR 1 Myong et al [37] 1 61 0/1 Trunk 1 S 1 NR 1 Maruyama et al [38] 1 43 0/1 Head&neck 1 S 1 NR 1 Hadjigeorgiou et al [39] 1 55 1/0 Trunk 1 ...…”
Section: Discussionmentioning
confidence: 99%
“…MRI revealed that T1weighted image (WI) signal was mostly an equal signal, T2WI signal was an iso-to-high signal [ 22 , 37 , 41 , 44 ]. Gadolinium enhancement T1WI showed enhancement of the tumor [ 22 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRI revealed that T1weighted image (WI) signal was mostly an equal signal, T2WI signal was an iso-to-high signal [ 22 , 37 , 41 , 44 ]. Gadolinium enhancement T1WI showed enhancement of the tumor [ 22 , 41 ]. The border of the tumor on the MRI was varied; some author reported well demarcated tumor [ 7 , 13 , 44 ], but the others were ill-defined [ 10 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…LGMS imaging also lacks characteristics of the most common CT and MRI manifestation as follows: mostly single lumps, lobulated or irregular type, a small number of tumor have clear border, mostly invasive growth, easy to infiltrate adjacent fat, fibrous and muscle tissues, visible necrosis and calcification; CT scan: non-contrast enhanced scan reveals uneven or lower density, and contrast enhanced scan reveals the uniform or thick-walled ring enhancement and mostly delayed enhancement [ 6 ] ; MRI characteristics: T1WI signal is mostly equal signal, T2WI signal is mostly slightly higher signal, the signal is not uniform, and there are cable-like signals. [ 7 ] Regarding to the 18 F-FDG PET/CT scan of LGMS, only Morii et al [ 8 ] have reported a case of back (left split muscle) LGMS, in which abnormally increased FDG metabolism can be seen in the lesions with an SUVmax of 9.8.…”
Section: Discussionmentioning
confidence: 99%